2009
DOI: 10.1002/jez.b.21278
|View full text |Cite
|
Sign up to set email alerts
|

Marfan syndrome and its disorder in periodontal tissues

Abstract: Elastic system fibers are composed of two distinct elements, elastin, which is an amorphous component crosslinked in the core, and microfibril, localized in the periphery of elastin. As microfibrillar proteins, fibrillins, microfibril-associated glycoproteins (MAGPs), latent TGF-beta-binding proteins (LTBPs), microfibril-associated proteins (MFAPs), and fibulins are known. Fibrillin-1 is a major microfibrillar protein and characterized by calcium binding EGF-like (cbEGF) domain. Association between fibrillin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
(29 reference statements)
1
28
0
3
Order By: Relevance
“…Interestingly, the fibers were mostly connected between the root and alveolar bone in a direction perpendicular to the tooth root axis. It has been reported that periostin expression in PDL is significantly decreased in fibrillindeficient mice, which exhibit loose connective tissue in the PDL 19,20) . In the present study, periostin was highly expressed in the PDL regenerated following application of 1 mg/ml fibrillin/ PGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the fibers were mostly connected between the root and alveolar bone in a direction perpendicular to the tooth root axis. It has been reported that periostin expression in PDL is significantly decreased in fibrillindeficient mice, which exhibit loose connective tissue in the PDL 19,20) . In the present study, periostin was highly expressed in the PDL regenerated following application of 1 mg/ml fibrillin/ PGA.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that fibrillin 1 and 2 are initially expressed at the surface of the developing root and widely observed in mature human PDL tissue 17) . Furthermore, a mutation in the Fibrillin-1 gene causes Marfan syndrome, which displays orofacial manifestations and increases susceptibility to periodontal disease 18,19) . It has also been shown that fibrillin plays an important role in maintaining the PDL through interactions with periostin and collagen 20) model, and evaluated the regenerated PDL by fibrillin application, histochemicaly.…”
Section: Introductionmentioning
confidence: 99%
“…PDGF alone, in particular the homodimer PDGF-BB, or in combination with IGF-I stimulated regeneration of periodontal ligament and its attachment to the alveolar bone [ 126 ], a matter of importance in Marfan patients with periodontitis. By the way, FGF2, discussed in more detail above, had similar effect on cells of the periodontal ligament [ 6 ]. PDGF was shown to improve healing and biomechanical parameters of acute injury of the medial collateral ligament in rabbits and rats, especially, if administered shortly after injury.…”
Section: Pdgfmentioning
confidence: 92%
“…Surgical repair is usually incomplete as well, resulting in decreased stiffness and adhesion formation [ 4 , 5 ]. Patients with Marfan syndrome also suffer from joint problems and from periondontitis, or infl ammation of the gingiva, periodontal ligament and alveolar bone loss which does not accompany dental caries [ 6 ]. Though less obvious than in other tissues, healing of tendons and ligaments occurs through two pathways.…”
Section: Basics Of Tendon Repairmentioning
confidence: 99%
See 1 more Smart Citation